Biosynthesis of nanosilver using Indian medicinal plants and evaluation of their antibacterial activity. (2015) - Lakshmipriya, T.; Meenambal, T.; Lavanyasri, R.; Nandhini, S.; Pavithra, N.; Swathi, S.; Uthra, I. Srivani
Phytosynthesised silver nanoparticles (AgNPs) were developed from silver nitrate (AgNO3 ) through a simple and eco-friendly route using the aqueous extracts of Indian medicinal plants Acacia nilotica, Solanum trilobatum and Punica granatum. The AgNP formation were characterised by using UV-Visible spectroscopy, atomic force microscopy (AFM), scanning electron microscopy (SEM), X-ray diffraction analysis (XRD) and energy dispersive X-ray spectroscopy (EDAX). The average particle size of the AgNPs synthesised from A. nilotica, S. trilobatum and P. granatum was determined to be 50, 110 and 60 nm, respectively. Anti-bacterial activity studies revealed that AgNPs synthesised from P. granatum exerted maximum effect against the few pathogenic and non-pathogenic bacterial strains. Phytochemical screening of the crude extracts of the three chosen plants identified tannins to be the active component responsible for the reduction of silver ions to nanoparticles. This study also revealed that green procedure would be preferred for large-scale operation with high biocompatibility.